Regional Economic Building Amidst Rising Protectionism and Economic Nationalism in ASEAN - Chandra, Alexander Christian (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
Despite its ambitious ASEAN Economic Community (AEC) project, protectionism and economic nationalism are on the rise in ASEAN. Protectionism, however, is not new to Southeast Asia, with governments across the region employ such an inward-looking economic policy when they enjoy economic stability, and pursue economic reform when confronted with major economic challenges. Unfortunately, embryonic industries will always exist in the region, and governments will find excuses to safeguard their existence. Consistent with the so-called 'Murdoch Schoold of critical political-economy' approach, this article mainly argues that the inclination towards protectionism in ASEDAN is primarily rooted in the domestic political-economy of ASEAN Member States. Apart from bringing about domestic regulatory changes, major economic liberalisationinitiatives of ASEAN, such as the ASEAN Free Trade Area and the AEC, significantly redistribute power and resources, and ignite struggles between competing domestic economic influences, many of which are in favour of government's protection. Whilst existing technical initiatives to address protectionism are useful, major crises that encourage major structural adjustments in all AMS might be needed to overcome fundamental protectionist inclination in the region